Psychosis and spirituality : consolidating the new paradigm - Clarke, Isabel; Wiley InterScience (Online service) (Chichester, West Sussex : John Wiley & Sons, 2010)
The new edition of this successful text builds on the very latest research to present an original and unique exploration of the psychology of both spirituality and psychosis. The editor brings together fascinating perspectives from a broad range of distinguished contributors.: This new edition covers the most recent body of research, both qualitative and quantitative, in its exploration of the interface between psychosis and spirituality, and investigation into anomalous experiences; Ten new chapters added and the remaining text completely updated; New to this edition is an expanded clinical s.
Psychosis and Spirituality Revisited: The Frontier is Opening up! / Isabel Clarke -- Section 1: Neuropsychology. Part Introduction -- The Neurophysiology of Religious Experience / Peter Fenwick -- Cognitive Neuroscience, Spirituality and Mysticism: Recent Developments / B Les Lancaster -- Section 2: Spirituality Revisited. Part Introduction -- The Polarities of Consciousness / Natalie Tobert -- Missing Stories: Psychosis, Spirituality and the Development of Western Religious Hermeneutics / Neil Douglas-Klotz -- Section 3: The Mystical Face of Psychosis: The Psychotic Face of Mysticism. The New Continuum. Part Introduction --'On Not Drinking Soup with a Fork': From Spiritual Experience to Madness to Growth : A Personal Journey / Peter K Chadwick -- Spiritual Experience: Healthy Psychoticism? / Gordon Claridge --'Psychopathology','Psychosis' and the Kundalini: Post-Modern Perspectives on Unusual Subjective Experience / Richard House -- Section 4: The Discontinuity Hypothesis and its Philosophical Implications. Part Introduction -- Psychosis and Spirituality: The Discontinuity Model / Isabel Clarke -- Knowledge and Reality / Chris Clarke -- Section 5: Research. Part Introduction -- Are Delusions on a Continuum? The Case of Religious and Delusional Beliefs / Emmanuelle Peters -- The Paradigm-Shifting Hypothesis: A Common Process in Benign Psychosis and Psychotic Disorder / Mike Jackson -- Transformative Crises / Caroline Brett -- Exploring the Transliminal: Qualitative Studies / Sharon Warwick, Roger Waldram -- Section 6: Clinical Implications. Part Introduction --'What is Real and What is Not': Towards a Positive Reconceptualisation of Vulnerability to Unusual Experiences / Isabel Clarke -- Visionary Spiritual Experiences / David Lukoff -- Learning to become Centred and Grounded and Let the Voices come and go / Nigel Mills -- Mapping Our Madness: The Hero's Journey as A Therapeutic Approach / Janice Hartley -- Spirituality, Psychosis and the Development of'Normalising Rationales' / David Kingdon, Ron Siddle, Farooq Naeem, Shanaya Rathod -- Endword / Isabel Clarke.
Includes bibliographical references and index.
Print version record.
Keywords: Psychoses -- Religious aspects; Psychiatry and religion; Psychotic Disorders; Delusions -- psychology; Religion and Psychology; Medicine; MEDICAL -- Psychiatry -- General; PSYCHOLOGY -- Psychopathology -- General; PSYCHOLOGY -- Clinical Psychology; PSYCHOLOGY -- Mental Illness; MEDICAL -- Mental Health; Electronic books